Target identification and validation of the alpha7 nicotinic acetylcholine receptor as a potential therapeutic target in retinal disease - Linn, David M. (Frontiers in Ophthalmology, 2023)
The role of acetylcholine (ACh) in visual processing in the mammalian retina has been the focus of research for many decades. Pioneering work on the localization of ACh discovered that the neurotransmitter is synthesized and stored in a distinct sub-population of amacrine (starburst) cells. Massey and Redburn (1982) proposed that ACh release is regulated to a low resting ‘tonic’ level, much like what is observed at the neuromuscular junction (NMJ). If there were a dysfunction in the tonic release of ACh, might post-synaptic changes render the targets of ACh (i.e. retinal ganglion cells, RGCs) vulnerable to disease? During my time at Pharmacia and Upjohn (PNU), selective nicotinic ACh receptor (nAChR) agonists (e.g. PNU-282987) were developed as a possible therapy for CNS diseases. Since RGCs are the main targets of neurodegeneration in glaucoma, could activation of this target provide neuroprotection? Therefore, experiments to identify alpha7 nAChRs in the retina (i.e. target ID) followed by ‘proof of concept’ experiments were conducted. Target ID studies included binding studies with retinal homogenates, [125I]-alpha-bungarotoxin (alpha-BTX) autoradiography and fluorescently tagged alpha-BTX binding in retinal slices. Imaging studies of intracellular calcium dynamics in the retinal slice were conducted. RT-PCR with alpha7 nAChR knock-out mice using the ‘laser-capture microdissection’ technique, in situ hybridization studies and RT-PCR analysis of human retina were conducted. Collectively, these experiments confirmed alpha7 aAChRs on specific cells in the retina. ‘Proof of concept’ neuroprotection studies demonstrated PNU-282987 provided significant protection of RGCs. This protection was dose-dependent and blocked with selective antagonists. More recently, evidence for the generation of new RGCs has been reported with PNU-282987 in rodents. Interestingly, the appearance of new RGCs is more pronounced with eye-drop application vs. intravitreal injection. One could postulate this reflects the neurogenic activation of alpha7 receptors on RPE (eye-drops) vs. a neuroprotective effect on RGCs (injections). In conclusion, there does appear to be a cholinergic retinal ‘tone’ associated with RGCs that could be utilized as a neuroprotective therapy. However, a distinct cholinergic neurogenic mechanism also appears to exist in the outer retina that could possibly be exploited to generate new RGCs lost through various disease processes.